The age of deleveraging : investment strategies for a decade of slow growth and deflation - Shilling, A. Gary. (Hoboken, N.J. : Wiley, 2011)
"Top economist Gary Shilling shows you how to prosper in the slow-growing and deflationary times that lie ahead. While many investors fear a rapid rise in inflation, author Gary Shilling, an award-winning economic forecaster, argues that the global economy is going through a long period of de-leveraging and weak growth, which makes deflation far more likely and a far greater threat to investors than inflation. Shilling explains in clear language and compelling logic why the U.S. and world economy will struggle for several more years and what investors can do to protect and grow their wealth in the difficult times ahead. The investment strategies that worked for last 25 years will not work in the next 10 years. Shilling advises readers to avoid broad exposure to stocks, real estate, and commodities and to focus on high-quality bonds, high-dividend stocks, and consumer staple and food stocks. . Written by one of today's best forecasters of economic trends-twice voted by Institutional Investor as Wall Street's top economistClearly explains what to invest in, what to avoid, and how to cope with a deflationary, slow-growth economy Demonstrates how Shilling has been consistently right about major economic trends since he began forecasting in the early 1980sFilled with in-depth insights and practical advice, this timely guide lays out a convincing case for why investors need to be prepared for a long period of weak growth and deflation-not inflation-and what you can do to prosper in the difficult times ahead"--
Machine generated contents note: Foreword. -- Acknowledgments. -- Introduction. -- Chapter 1: Spotting Bubbles. -- Chapter 2: Making Great Calls. -- Chapter 3: The Housing Bubble (Great Call #6). -- Chapter 4: The Financial Bubble (Great Call #7). -- Chapter 5: The Results of Denial. -- Chapter 6: Slow Growth Ahead. -- Chapter 7: No Help from Anywhere. -- Chapter 8: Chronic Worldwide Deflation. -- Chapter 9: Monetary and Fiscal Excesses. -- Chapter 10: The Outlook for Stocks. -- Chapter 11: 12 Investments to Sell or Avoid. -- Chapter 12: 10 Investments to Buy. -- About the Author. -- Index.
Includes index.
Keywords: Investments -- United States; Investment analysis -- United States; Deflation (Finance) -- United States; Economic forecasting -- United States; United States -- Economic conditions -- 2009-